Prevalence, characterisation and potential origin of Escherichia coli found in surface and ground waters utilized for irrigation of fresh produce - Schoeman, Nika Anna (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc Food Sc)--Stellenbosch University, 2013.